Hot Springs Characterization In Peninsular Malaysia Using Integrated Geophysical Methods - Samsudin, Nuraisyah (2023)
In regions renowned for geothermal activity, the presence and characteristics of hot springs are intricately linked to underlying geological discontinuities, primarily faults, fractures, and shear zones. This study harnesses the prowess of ground magnetic, 2-D resistivity imaging, and induced polarization methods to discern these deep-seated geological structures, which significantly influence the distribution and properties of hot springs. The methods applied provided nuanced insights into the subsurface, mapping the intricate interplay between faults and the resultant geothermal manifestations. Specifically, ground magnetic and 2-D resistivity imaging were employed to trace the trajectory of these faults in the heart of geothermal zones, enhancing the fidelity of existing geological representations and pinpointing potential geothermal surfaces. Such detailed analyses are pivotal, especially when evaluating the depth of magnetic anomalies which symbolize these vital structural underpinnings. Induced polarization emerged as a critical tool, effectively differentiating between geothermal mud (clay) and groundwater, a distinction often blurred when solely relying on 2-D resistivity imaging. Three geothermal hotbeds were the focal points of this research: Lojing Highlands in Kelantan, Manong in Perak, and Ladang Kombok in Negeri Sembilan. In the Lojing Highlands, magnetic residuals unveiled a fault line trending NE-SW, marked by contrasts ranging from 10 nT to 120 nT. Manong's geological fabric similarly exhibited a NE-SW trending fault, with magnetic nuances spanning from 10 nT to 120 nT.